RANGE AND IMAGE DATA INTEGRATION FOR MAN-MADE OBJECT RECONSTRUCTION - F. Nex; F. Remondino (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2013)
The extraction of information from image and range data is one of the main research topics. In literature, several papers dealing with this topic has been already presented. In particular, several authors have suggested an integrated use of both range and image information in order to increase the reliability and the completeness of the results exploiting their complementary nature. In this paper, an integration between range and image data for the geometric reconstruction of man-made object is presented. In particular, the focus of this paper is on the edge extraction procedure performed in an integrated way exploiting the information provided by both range and image data. Both terrestrial and aerial applications have been analysed for the façade extraction in terrestrial acquisitions and the roof outline extraction from aerial data. The algorithm and the achieved results are described and discussed in detail.